Critical Literacy in Canada: A Systematic Review of Curricula and Literature - Kaya, Jean; Dressler, Roswita; Lenters, Kim (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2022)
Critical literacy is a pedagogy that serves to mediate social justice issues and educate for transformative social action. We present a systematic review of how critical literacy has been incorporated in Canada’s provincial/territorial curriculum documents since the late 1990s and integrated in K-12 classrooms in the last decade. Our analysis shows that critical literacy has been addressed with varying degrees of explicitness in curricula, and there is an imbalance of studies on critical literacies among provinces and territories. We discuss implications and encourage stakeholders in education to explicitly embed critical literacy into curricula and promote critical literacy practices in the classroom.